The Home System of Practice - Eon, Christine (Curtin University, 2017)
This thesis investigates the interactions between occupants and the physical built environment and their impact on resource use. Elements of practice theory, socio-psychology, urban ecology and life cycle assessment were combined to provide a holistic perspective of the home and in particular, occupant behaviour, everyday practices and routines. The results were based on a two year longitudinal study of ten Australian living laboratories consisting a mix of older and modern energy efficient residential homes.